THE EFFECT OF THIDIAZURON (TDZ) ON SHOOT REGENERATION OF ASTRAGALUS SCHIZOPTERUS - M. Yorgancilar; S. Erisen (Journal of Animal and Plant Sciences, 2011)
The effect of thidiazuron (TDZ) on shoot regeneration of the endemic Astragalus schizopterus was investigated in Turkish flora. Explants (leaf and petiole) were cultured on the basic medium Murashige and Skoog (MS) containing various plant growth regulators (PGRs) [0.0, 0.4, 0.5, 0.6 mg l-1 thidiazuron (TDZ); 0.4, 0.5, 0.6 mg l-1 TDZ x 0.1, 0.2 mg l-1 α-naphthaleneacetic acid (NAA)] to induce shoot bud induction. The combinations and concentrations of PGRs showed significant variations for the frequency of callus formation, appearance of callus and the potential of callus differentiation. Callus formation occurred in cultures, but it was not obtained in adventitious shoot regeneration. Therefore, rapid multiplication was made by using lateral meristem which were obtained from 4 weeks sterile seedling. Lateral meristems were cultured on basic media MS containing various PGRs 0.5, 1.0 mg l-1 zeatin (ZEA), benzyladenine (BA) and 0.22, 0.5 and 1 mg l-1 TDZ. The highest number of shoots (23.6/explants) was obtained on MS medium containing 1 mg l-1 TDZ followed by MS medium cointaining 1 mg l-1 BA which produced 15.80 shoots per explant. It was observed that shoots didn’t have healthy development in all media containing TDZ. So it was suggested that BA is a useful PGR for rapid multiplication in A. schizopterus. The regenerated shoots were transferred to rooting medium [MS with 0.5-1 mg l-1 NAA and 0.5-1 mg l-1 indole-3-butyric acid (IBA)] where they successfully rooted (100%) and showed rapid elongation. Rooted shoots were transferred to the ex vitro and produced normal plants.
Keywords: Astragalus; endemic; lateral meristem; micropropagation; callus induction.